2000
DOI: 10.2337/diabetes.49.11.1897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differing durations of antecedent hypoglycemia on counterregulatory responses to subsequent hypoglycemia in normal humans.

Abstract: The aim of this study was to determine whether the duration of antecedent hypoglycemia regulates the magnitude of subsequent counterregulatory failure. A total of 31 lean healthy overnight-fasted individuals (16 men/15 women) were studied. There were 15 subjects (8 men/7 women) who underwent two separate 2-day randomized experiments separated by at least 2 months. On day 1, 2-h hyperinsulinemic (9 pmol · kg -1 · min -1 ) euglycemic (5.2 ± 0.1 mmol/l) or hypoglycemic (2.9 ± 0.1 mmol/l) glucose clamps (prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 55 publications
7
64
1
1
Order By: Relevance
“…The origin of hypoglycemic symptoms during hypoglycemia is complex. Previous studies demonstrated scenarios whereby discordant responses between autonomic symptoms and catecholamine responses can exist during hypoglycemia (17,(31)(32)(33). Generally, studies have determined that autonomic symptoms can be preserved despite reduced activity in other branches of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of hypoglycemic symptoms during hypoglycemia is complex. Previous studies demonstrated scenarios whereby discordant responses between autonomic symptoms and catecholamine responses can exist during hypoglycemia (17,(31)(32)(33). Generally, studies have determined that autonomic symptoms can be preserved despite reduced activity in other branches of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of muscle sympathetic nerve activity. Muscle sympathetic nerve activity (MSNA) was recorded from the peroneal nerve at the level of the fibular head and popliteal fossa (16,17). The approximate location of this nerve was determined by transdermal electrical stimulation to produce painless muscle contraction of the foot.…”
Section: Methodsmentioning
confidence: 99%
“…This reduction in counterregulatory responses occurs after as little as one episode of hypoglycemia (Heller & Cryer, 1991;Robinson, Parkin, MacDonald, & Tattersall, 1995). Other investigators demonstrated this phenomenon after repeated episodes of hypoglycemia delivered on consecutive days (2 days, blood glucose averaging 45 mg/dl for 60 min each day) (Widom & Simonson, 1992) or two episodes in a single day involving morning and afternoon sessions (hypoglycemia ranging from 52 to 70 mg/dl maintained for up to 2 hr in each session) (Davis et al, 2000;Davis, Shavers, Mosqueda-Garcia, & Costa, 1997). These studies support the concept that recent hypoglycemia acutely induces HAAF in humans (Cryer, 2001).…”
Section: Face Validity Of Rodent Haaf Studiesmentioning
confidence: 99%
“…All of these studies report suppression of hypoglycemia-induced epinephrine secretion after prior hypoglycemia, and most report similar declines in hypoglycemia-induced norepinephrine, glucagon, growth hormone, and cortisol secretion. When hypoglycemic symptoms were assessed, these responses were also reduced after prior hypoglycemia (Davis et al, 2000;Heller & Cryer, 1991;Widom & Simonson, 1992).…”
Section: Face Validity Of Rodent Haaf Studiesmentioning
confidence: 99%
“…Following this, euglycaemia was restored once more by decreasing the insulin infusion rate and gradually reducing the glucose infusion rate. The depth and duration of this hypoglycaemic episode were chosen on the basis that they were expected to attenuate glucoregulatory hormone responses to a subsequent stimulus such as moderate-intensity exercise or hypoglycaemia [22,25,26]. At time intervals before and during euglycaemia and hypoglycaemia, blood samples were collected for the assessment of glucoregulatory hormone levels.…”
Section: Methodsmentioning
confidence: 99%